2020
DOI: 10.32378/ijp.v4i2.192
|View full text |Cite
|
Sign up to set email alerts
|

Improving Critical Listening skills in EMT Students

Abstract: <p>Introduction: Although the importance of EMT students utilizing critical listening skills is apparent, there is little research focused on EMT students or EMTs and critical listening. Ensuring EMT students develop critical listening skills can be an asset that reaches beyond the goal of improving their education. It also has the potential to improve the quality of care they go on to deliver. EMTs may have the only verbal contact with the patient while they are still conscious, or with bystanders that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…In agreement with the research findings of Chang (2009), Moreno andMoyer (2010), Ferrari-Bridgers, Stroumbakis, et al (2017), and Armstrong and Ferrari-Bridgers (2019), the data from this study showed that students performed better when assessed in a dual listening and reading modality. The fact that students performed better in a dual modality suggests that adding a listening component to a test helps students better recall and retain information.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with the research findings of Chang (2009), Moreno andMoyer (2010), Ferrari-Bridgers, Stroumbakis, et al (2017), and Armstrong and Ferrari-Bridgers (2019), the data from this study showed that students performed better when assessed in a dual listening and reading modality. The fact that students performed better in a dual modality suggests that adding a listening component to a test helps students better recall and retain information.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this present study confirmed the findings of Peterson (2007), Ferrari-Bridgers, Stroumbakis, et al (2017, and Armstrong and Ferrari-Bridgers (2019) suggest that simply integrating a listening component into a test has a positive impact on student learning and performance.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations